2023
DOI: 10.1155/2023/7768704
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Efficacy of Intravenous Ibuprofen in the Treatment of Postoperative Acute Pain: A Phase III Multicenter Randomized Placebo-ControlledDouble-Blind Clinical Trial

Abstract: Objective. To evaluate the analgesic efficacy and safety of different does of intravenous ibuprofen (IVIB) in the treatment of postoperative acute pain. Methods. Patients with an intravenous (IV) patient-controlled analgesia device after abdominal or orthopedic surgery were randomly divided into placebo, IVIB 400 mg, and IVIB 800 mg groups. The first dosage of study medicines was given intravenously 30 minutes (min) before surgery ended, followed by six hours (h) intervals for a total of eight doses following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Administration of IV ibuprofen preoperatively and postoperatively has also been shown to significantly reduce pain and morphine consumption in patients who underwent elective, single-site orthopaedic or abdominal surgery. 32,33 Finally, Zhou et al 34 has recently shown that intermittent administration of IV ibuprofen within 24 hours postoperatively significantly decreased morphine use and VAS pain scores in patients undergoing orthopaedic or abdominal surgery.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Administration of IV ibuprofen preoperatively and postoperatively has also been shown to significantly reduce pain and morphine consumption in patients who underwent elective, single-site orthopaedic or abdominal surgery. 32,33 Finally, Zhou et al 34 has recently shown that intermittent administration of IV ibuprofen within 24 hours postoperatively significantly decreased morphine use and VAS pain scores in patients undergoing orthopaedic or abdominal surgery.…”
Section: Discussionmentioning
confidence: 97%
“…1,49,50 NSAIDs offer a promising analgesic for managing acute and perioperative pain, where perioperative NSAIDs use has been shown to decrease pain and short-term opioid use after surgery. 14,15,19,24,25,34,51 The presented study provides insight into the effect of a scheduled low-dose, short-term IV NSAID regimen on opioid use and pain over a 5-day treatment period in orthopaedic polytrauma patients. Although it has been shown that scheduled IV NSAID use during the first 2 inpatient days after orthopaedic trauma can be opioid-sparing and provide adequate analgesia, 31 our group was able to demonstrate that this can be achieved further in orthopaedic polytrauma patients during the first 5 inpatient days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation